Implementasi Data Mining Menggunakan Algoritma Apriori Dalam Menentukan Pola Penjualan - Handoyo, Joko; Rafiqasha, Reyhan Maulana; Joko Handoyo (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2024)
Toko Singgah Mata, a company that sells safety and security equipment, located in Kendilan Sambong Village, is facing several problems that require creative solutions. One of the main problems is the uncomputerization of business processes and the high stock of unsold goods due to a lack of buyer attraction. Shop owners need to develop creative ideas to increase sales by arranging ordering patterns that are attractive to consumers. In an effort to increase the efficiency of preparing order patterns, shops can utilize data mining techniques. By using the Apriori algorithm, transaction data from interviews with shop staff can be processed to determine the most effective combination in product sales. The analysis was carried out on transaction data from January to June 2023, involving 122 Singgah Mata store transactions. The results of analysis using the Apriori algorithm produce four association rules based on parameters with a minimum support value of 10% and a minimum confidence value of 10%. The lift ratio value obtained is greater than 1, indicating that the rule has a positive correlation. The application of the Apriori algorithm to the Singgah Mata store information system produces results that are consistent with manual analysis. This system proves its usefulness in forming an effective sales strategy. With a trial success rate of 89.2%, the functional results of the tested cases show excellent system performance, giving confidence that the application of this technology can make a positive contribution to increasing sales and operational efficiency of Singgah Mata stores.